Menguak Realitas Jejak “Goah” Sebagai Simbol Sakralitas Pertanian Di Desa Ciasmara Kecamatan Pamijahan Kabupaten Bogor - Supriatna, Raden Atang; Nugraha, Yogaprasta Adi (JHP17 (Jurnal Hasil Penelitian), 2022)
Agriculture is one of the important sectors that contribute to national income. However, agricultural development currently has a tendency to increase productivity so that it impacts on the agricultural system which tends to make agriculture is more just an activity that produces agricultural "commodities" Mainstreaming agriculture into "commodity agriculture" has an impact on the destruction of cultural infrastructure supporting agriculture. This study aims to: Identify "Goah" in Ciasmara Village, Pamijahan District, Bogor Regency. This study uses a Rapid-Ethnography approach, located in the village of Ciasmara, Pamijahan District, Bogor Regency from March 2019 - August 2019. This research found that in Ciasmara village there is still a "goah", but its form is no longer limited to a special space where to place rice but the "Goah" has transformed into another form such as a bucket or a special drum. The transformation form of the "Goah" is a result of the limitations of domestic space and the shift in the value of agricultural sacredity in the village.